Comprehensive Phenolic and Free Amino Acid Analysis of Rosemary Infusions: Influence on the Antioxidant Potential - Juliana A. Barreto Peixoto; Gerardo Álvarez-Rivera; Rita C. Alves; Anabela S. G. Costa; Susana Machado; Alejandro Cifuentes; Elena Ibáñez; M. Beatriz P. P. Oliveira (MDPI AG, 2021)
The phenolics profile, free amino acids composition, and antioxidant potential of rosemary infusions were studied. Forty-four compounds belonging to nine different groups (hydroxybenzoic acids, hydroxycinnamic acids, flavan-3-ols, flavanones, flavones, phenolic diterpenes, hydroxybenzaldehydes, coumarins, and pyranochromanones) were identified by UHPLC-ESI-Q-TOF-MS. Of these, seven were firstly described in rosemary infusions: a rosmanol derivative, two dihydroxycoumarin hexosides, a hydroxybenzaldehyde, a dihydroxybenzoic acid hexoside, coumaric acid hexoside, and isocalolongic acid. The free amino acid profile of the beverages was also reported by the first time with seven amino acids found (asparagine, threonine, alanine, tyrosine, phenylalanine, isoleucine, and proline). Furthermore, DPPH• scavenging ability, Ferric Reducing Antioxidant Power and Oxygen Radical Absorbance Capacity, as well as total phenolics and flavonoids contents, were assessed. Overall, rosemary infusions showed to be a very good source of antioxidants. A 200 mL cup of this infusion contributes to the ingestion of ~30 mg of phenolic compounds and about 0.5-1.1 μg of free amino acids. This type of beverages may present a positive impact on the maintenance of the body antioxidant status and contribute to the prevention of oxidative stress related diseases.